2015
DOI: 10.1111/ajo.12407
|View full text |Cite
|
Sign up to set email alerts
|

Disordered eating attitudes and exercise in women undergoing fertility treatment

Abstract: Contrary to previous research, our findings do not confirm a greater lifetime prevalence rate of eating disorders in women attending an infertility clinic. This study does highlight the importance of screening women with forms of an ovulatory disorder for features of disordered eating attitudes and driven exercise behaviours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…This suggests the women's QOL, particularly their medical status was related to their obesity. Non-obese women with PCOS were more preoccupied with controlling their eating and body weight; a major feature of women with eating disorders [11].…”
Section: Discussionmentioning
confidence: 99%
“…This suggests the women's QOL, particularly their medical status was related to their obesity. Non-obese women with PCOS were more preoccupied with controlling their eating and body weight; a major feature of women with eating disorders [11].…”
Section: Discussionmentioning
confidence: 99%
“…he impact of modifiable lifestyle factors such as age, smoking, drinking, caffeine, and weight status on reproductive outcomes is widely known (1,2). Under the rubric of preconception care, however, remains the little investigated topic of eating disorders within a fertility population (3)(4)(5). Eating disorders are serious mental illnesses related to weight and shape concerns, problematic eating behaviors, and maladaptive weight control behaviors that occur in women of childbearing years (6,7).…”
mentioning
confidence: 99%
“…In contrast, a Danish cohort study of women who were treated using assisted reproductive technology found a similarly low rate of hospitalization due to eating disorders as that found in the general population (Assens et al, 2015). Although an Australian study involving women undergoing infertility treatment found no global difference in the rate of self-reported eating disorders, it revealed that women with an ovulatory disorder or PCOS scored higher on the eating disorder examination questionnaire (EDE-Q) (Rodino et al, 2016). Disturbance of ovarian function in women with eating disorders is not limited to women with anorexia nervosa but can also be found in women with bulimia nervosa and binge eating disorder.…”
Section: Eating Disorders and Infertilitymentioning
confidence: 96%